Chest Radiographic Findings in Pediatric Patients with Intraluminal Pulmonary Vein Stenosis. (18th June 2013) - Mayhew, Caitlin E.; Lee, Edward Y.; Balasubramanian, Sowmya; Muneeb, Muhammad; Gauvreau, Kimberlee; Tracy, Donald A.; Jenkins, Kathy J.
Abstract Early recognition of pulmonary vein stenosis (PVS) is crucial for optimizing clinical outcomes. Our goal was to characterize radiographic patterns specific to pediatric patients with PVS to facilitate early detection. Patients and Methods Pediatric patients with multivessel (≥2) intraluminal PVS were identified from a single‐center registry. Initial chest radiographs were reviewed. Radiographic findings were summarized using frequencies and percentages for categorical data, and medians and ranges for continuous data. Interrater agreement was assessed using kappa statistics. Results Chest radiographs of 41 PVS patients were evaluated; median age at presentation 5.2 (0.5–102.6) months. Underlying congenital heart disease was present in 31 (76%), lung disease in four (10%), and neither in six (15%). Common heart diseases were hypoplastic left heart syndrome (five, 12%), totally anomalous pulmonary venous connection (nine, 22%), and heterotaxy (five, 12%). PVS was bilateral in 22 (54%), right‐sided in six (14%), and left‐sided in 13 (32%). All chest radiographs were abnormal. Increased interstitial opacity was present in all patients, reticular opacity in 35 (85%), and ground‐glass opacity in 29 (71%). Consolidation (one, 2%), pleural effusions (four, 10%), and nodular opacities (0) were unusual. Distributional heterogeneity was common (17, 42%). Interrater agreement was generally high (kappa >0.84) except for lobe location. Findings were similar among patients with isolated PVS, PVS with congenital heart disease, and PVS with lung disease. Conclusion Diagnosis of PVS should be considered in infants with increased interstitial opacity, reticular opacity, and ground‐glass opacity on chest radiography, especially if findings are heterogeneous.